Fourth Five Year Plan Report of the Working Group for Transport Equipment - Planning Commission (Planning Commission, 1968)
In the group of machinery and equipment forming part of investment. Transport equipment is one of The most important in terms of value and for its significance for the growth of various sectors of economy. The industries engaged in the manufacture of transport equipment have made significant progress in the last decade and it may be safely stated that in another decade, not only will India become self-sufficient, but would be able to export various transport equipments in substantial quantities. It is estimated that by 1965-66, the output of transport equipment would be approximately Rs. 2,800 million (automobiles Rs. 1,600 million, railways Rs. 1,200 million) and the output by the end of Fourth Plan may approximately be Rs. 5400 million (automobiles Rs. 3,600. railways Rs. 1,800) accounting for nearly one fourth of the total requirement of machinery and equipment for investment in the entire economy.
Report of the Working Group for Transport Equipment
Planning Group on Machinery Industries